The elusive fan : reinventing sports in a crowded marketplace - Rein, Irving J. (McGraw-Hill, 2006)
Sports are a multibillion-dollar global business that will continue to grow by leaps and bounds into the foreseeable future. The bad news is: It's never been harder to attract, engage, and retain the sports fan. Today's sports fans are bombarded by choices. Traditional sports, such as baseball, football, and basketball, compete for fans' dollars with snowboarding, lacrosse, poker...even paintball. The old business formulas, developed in the age of three TV networks and creaky stadiums, no longer apply. World-renowned communication expert Irving Rein, international marketing guru Philip Kotler, and communication specialist Ben Shields deliver an innovative new business model centered squarely on fan satisfaction and retention. They give you the tools to transform your sports product into an enduring brand-immune to the vagaries of winning and losing-that quickly adapts to changing market conditions. Along the way they illustrate their points with fascinating case studies, including Manchester United's transformation from a plucky home team to a billion-dollar international franchise Professional golf phenomenon Michelle Wie's quest to maximize her talents and marketability Southlake Carroll High School football team's benchmarking of professional and college football programs to build its own brand Daytona International Speedway's reinvention of fan intimacy Combining expert analysis with field-tested strategies for winning hearts and minds, The Elusive Fan is your guide to surviving and thriving in today's ever-widening world of sports.